1996
DOI: 10.3138/cmlr.53.1.281
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Vocabulary: An Exploratory Study of Direct Techniques

Abstract: Incidental learning of vocabulary from context while reading is a major avenue to lexical growth in either a first or second language (Day, Omura, & Hiramitsu, 1991; Jenkins, Stein, & Wysocki, 1984; Krashen, 1989; Nagy, Anderson, & Herman, 1987; Schouten-van Parreren, 1989). There is growing evidence to suggest, however, that inferring the meaning of new vocabulary in context is a lengthy and error-prone undertaking which, by itself, is an inefficient way of mastering second language vocabulary. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Thus, metacognitive or metalinguistic instruction that aims at raising students' awareness of the internal structures of morphologically complex words might be beneficial for students. Some studies, in fact, argue the potential benefits of metacognitive vocabulary instruction (Harley, Howard, & Roberge, 1996;Tréville, 1996). In dealing with metacognition, teachers should take advantage of students' awareness of the importance of contextual clues because it could act as a control against overreliance on kanji clues (Mori, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, metacognitive or metalinguistic instruction that aims at raising students' awareness of the internal structures of morphologically complex words might be beneficial for students. Some studies, in fact, argue the potential benefits of metacognitive vocabulary instruction (Harley, Howard, & Roberge, 1996;Tréville, 1996). In dealing with metacognition, teachers should take advantage of students' awareness of the importance of contextual clues because it could act as a control against overreliance on kanji clues (Mori, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…However, this sort of contextual learning has been found to be low in efficiency (Coady 1993;Qian 1996). The reading-based context created with a single or several readings cannot support learners' sustained, multiple encounters with the new words (Harley et al 1996). Faced with assigned reading material, learners often lack the motivation to process the text deeply, and thus fail to learn the new words embedded in the texts (Sun and Dong 2004), and there is limited opportunity to use the new words for authentic, communicative purposes.…”
Section: Knowledge Buildingmentioning
confidence: 97%
“…A number of studies have reported the positive effects of concept mapping in a variety of instructional settings. For example, it has been used as a technique for increasing vocabulary (Harley et al, 1996;Johnson and Steele, 1996;Morin and Goebel, 2001), improving reading comprehension (Baumann and Bergeron, 1993;Carrell et al, 1989;Lipson, 1995;Tang, 1992) and writing skills (Cronin et al, 1992;Schultz, 1991), and facilitating the comprehension of concepts in subject areas (Parkes et al, 1999;Patterson, 2001;Roth, 1994). Concept mapping also helps students in special education programmes to promote their literacy knowledge (Boyle, 1996;Englert and Mariage, 1991;MacArthur, 1996;Sinatra et al, 1994).…”
Section: Concept Mapping As a Form Of Pre-task Planningmentioning
confidence: 99%